Biomass Carbon Content in Schima- Castanopsis Forest of Midhills of Nepal: A Case Study from Jaisikuna Community Forest, Kaski - Tripathi, Sushma; Thapa, Chandra Bahadur; Sharma, Amrit; Paudel, Ganesh (International Journal of Environment, 2018)
Community forests of Nepal’s midhills have high potentiality to sequester carbon. This paper tries to analyze the biomass carbon stock in Schima-Castanopsis forest of Jaisikuna community forests of Kaski district, Nepal. Forest area was divided into two blocks and 18 sample plots (9 in each block) which were laid randomly. Diameter at Breast Height (DBH) and height of trees (DBH≥5cm) were measured using the DBH tape and clinometer. Leaf litter, herbs, grasses and seedlings were collected from 1*1m2 plot and fresh weight was taken. For calculating carbon biomass is multiplied by default value 0.47. The AGTB carbon content of Chilaune, Katus and other species were found 19.56 t/ha, 18.66 t/ha and 3.59 t/ha respectively. The AGTB of Chilaune dominated, Katus dominated and whole forest was found 43.78 t/ha, 39.83 t/ha and 41.81 t/ha respectively. Carbon content at leaf litter, herbs, grasses and seedlings was found 2.73 t/ha. Below ground biomass carbon at whole forest was found 6.27 t/ha. Total biomass and carbon of the forest was found 108.09 t/ha and 50.80 t/ha respectively. Difference in biomass and carbon content at Chilaune dominated block and Katus dominated block was found insignificant. This study record very low biomass carbon content than average of Nepal’s forest but this variation in carbon stock is not necessarily due to dominant species present in the forest. Carbon estimation at forest of different elevation, aspect and location are recommended for further research. International Journal of Environment Volume-6, Issue-4, Sep-Nov 2017, page: 72-84